The new treaty on patents, genetic resources and associated traditional knowledge - Chiarolla, Claudio (2024)
Recording of webinar convened by the Legal Affairs Office of the CGIAR System Organization and the CGIAR Genebank Initiative, held on 6 June 2024, with guest speakers Wend Wendland (Secretary of the Intergovernmental Committee on Genetic Resources, Traditional Knowledge, Folklore (IGC), and Director of the Traditional Knowledge Division at WIPO (Geneva, Switzerland), who led the negotiation of the international instrument in question) and Preston Hardison (Policy Analyst at the Tebtebba Foundation (Baguio City, Philippines), and representative of the International Indigenous Forum on Biodiversity, and Indigenous Peoples and Local Communities at international fora).